Determinants of the acquisition of smaller firms by larger incumbents in high-tech industries: Are they related to innovation and technology sourcing? - Marcus Wagner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
Innovation activities in high tech industries provide considerable challenges for technology and innovation management. In particular, firms frequently face significant technological challenges since these industries has a long history of radical innovations which are taking place through distinct industry cycles of higher and lower demand. The paper investigates these issues for three high-tech industries, namely semiconductor manufacturing, biotechnology and electronic design automation which is a specific sub-segment of the semiconductor industry. It analyses the association of firm characteristics with different aspects of acquisition behaviour. Particular focus is put on innovation-related firm characteristics. The paper finds that the determinants for acquisitions are mostly related to firm size, financial conditions and geographical origin of the firm. Only for biotechnology, a substitutive relationship is identified between acquisitions and own research activities.
Keywords: L10; L86; M20; 330; acquisition; innovation; semiconductor; design; automation; biotechnology; Übernahme; Klein- und Mittelunternehmen; Hochtechnologiesektor; Innovation; Welt